Debating Dissent: Canada and the 1960s - Azzi, Stephen; Boudreau, Michael; Campbell, Lara; Carstairs, Catherine; Dyck, Erika; Gidney, Catherine; Hayday, Matthew; Hewitt, Steve; Igartua, José E.; Lexier, Roberta; Martel, Marcel; McInnis, Peter S. (Peter Stuart); et al. (Canadian social history series, 2012)
Although the 1960s are overwhelmingly associated with student radicalism and the New Left, most Canadians witnessed the decade's political, economic, and cultural turmoil from a different perspective. Debating Dissent dispels the myths and stereotypes associated with the 1960s by examining what this era's transformations meant to diverse groups of Canadians - and not only protestors, youth, or the white middle-class.With critical contributions from new and senior scholars, Debating Dissent integrates traditional conceptions of the 1960s as a 'time apart' within the broader framework of the 'long-sixties' and post-1945 Canada, and places Canada within a local, national, an international context. Cutting-edge essays in social, intellectual, and political history reflect a range of historical interpretation and explore such diverse topics as narcotics, the environment, education, workers, Aboriginal and Black activism, nationalism, Quebec, women, and bilingualism. Touching on the decade's biggest issues, from changing cultural norms to the role of the state, Debating Dissent critically examines ideas of generational change and the sixties. --Publisher's description

Aboriginal History: A Reader - Burnett, Kristin; Reid, Geoff (Oxford University Press, 2012)
Combining contemporary articles with historical documents, this engaging reader examines the rich history of Canada's Aboriginal peoples. The 30 articles - half of which are original to this volume - explore a diverse range of topics, including spirituality, colonialism, self-identity, federal policy, residential schools, labour, and women's rights. With in-depth coverage of events and processes from the earliest times through to the modern day, [the reader] offers students a new appreciation for the long and complex history of Canada's First Nations, Métis, and Inuit peoples. --Publisher's description
Keywords: Indians of North America -- Canada -- Historiography

Saving for Retirement: Intention, Context, and Behavior - Clark, Gordon L.; Strauss, Kendra; Knox, Janelle Kallie (Oxford University Press, 2012)
Understanding the ways in which people save for their retirement is an urgent issue. So much has changed in the last 10 to 15 years, especially in the area of the provision of pensions and retirement income. Around the world, greater and greater responsibility is being allocated to individuals while governments discount their contributions to social security and employers retreat from the provision of supplementary retirement income. This book explores the behavioral revolution and its implications for understanding financial decision-making and saving for the future. Recognizing the profound implications of this research program, it goes beyond issues of risk aversion, framing, and decision-making to consider how social identity and the resources due to people by virtue of their place in society figure in savings behavior. It gives considerable attention to the context of the environment in which people make financial decisions, arguing that this allows a better understanding of the coexistence of sophistication and naivety apparent in patterns of retirement saving. Utilizing databases from the UK, the book provides an empirical foundation to its theoretical arguments, demonstrating how an integrated approach to individual financial decision-making is necessary if we are to address the apparent shortfall in many people's planning for the future. The book concludes by setting the agenda for the design, governance, and regulation of pension savings schemes consistent with delivering cost-effective solutions to pension adequacy. In these ways, it sets forth a strategy for rethinking individual behavior as well as the design of retirement income systems. --Publisher's description
Keywords: Altersversorgung; Finance, Personal Decision making; Pensions; Rentenversicherung; Retirement income Planning Psychological aspects; Revenu de retraite Planification Aspect psychologique; Soziale Sicherheit; Sparen; pensions (compensation)

Governing Cultures: Anthropological Perspectives on Political Labor, Power, and Government - Coulter, Kendra; Schumann, William R. (Palgrave Macmillan, 2012)
Governments are formal political institutions, places of work for thousands of women and men, and powerful social, cultural, and economic sites that shape the lives of all people. This collection demonstrates how anthropologists enrich our understandings of government by exploring the labor of those who govern, and how the dynamics of culture are at the heart of government actions that justify, modify, and reproduce political action. By assembling original, ethnographically-grounded research in legislatures, executives, and bureaucracies, this volume illuminates and unpacks the structures, practices, and values of government actors in local, regional, and national contexts. It will be of interest to scholars and students in anthropology, as well as sociology, political science, policy studies, and labor studies. --Publisher's description
Keywords: Anthropologie politique; Government policy; Legislative power; Political anthropology; Pouvoir législatif

Labour Goes to War: The CIO and the Construction of a New Social Order, 1939-45 - Cuthbertson, Wendy (Studies in Canadian military history, 2012)
During the Second World War, the Congress of Industrial Organizations in Canada grew from a handful of members to more than a quarter-million and from political insignificance to a position of influence in the emergence of the welfare state. What was it about the "good war" that brought about this phenomenal growth? And how did this coming of age during the war affect the emerging CIO? Labour Goes to War analyzes the organizing strategies of the CIO during the war to show that both economic and cultural forces were behind its explosive growth. Labour shortages gave workers greater power in the workplace and increased their militancy. But workers’ patriotism, their ties to those on active service, memories of the First World War, and allegiance to the "people’s war" also contributed to the CIO’s growth - and to what it claimed for workers. At the same time, union organizers and workers influenced one another as the war changed lives, opinions, expectations - and notions of women’s rights. Drawing on an impressive array of archival material, Wendy Cuthbertson illuminates this complex wartime context. Her analysis shows how the war changed lives, opinions, and expectations. She also shows how the complex, often contradictory, motives of workers during this period left the Canadian labour movement with an ambivalent progressive/conservative legacy. --Publisher's description
Keywords: 20th century. Labor unions; 20th century. Syndicalisation; Canada; Histoire; History; Labor Unions; Ontario; Organizing; Organizing. Labor unions; Political activity; Political activity. Social conditions

Raising the Workers' Flag: The Workers' Unity League of Canada, 1930-1936 - Endicott, Stephen Lyon (University of Toronto Press, 2012)
During the Great Depression, the conflicting interests of capital and labour became clearer than ever before. Radical Canadian workers, encouraged by the Red International of Labour Unions, responded by building the Workers' Unity League – an organization that greatly advanced the cause of unions in Canada, and boasted 40,000 members at its height. In Raising the Workers' Flag, the first full-length study of this robust group, Stephen L. Endicott brings its passionate efforts to light in memorable detail. Raising the Workers' Flag is based on newly available or previously untapped sources, including documents from the Royal Canadian Mounted Police's Security Service and the Communist Party's archives. Using these impressive finds, Endicott gives an intimate sense of the raging debates of the labour movement of the 1930s. A gripping account of the League's dreams and daring, Raising the Workers' Flag enlivens some of the most dramatic struggles of Canadian labour history. -- Publisher's description
Keywords: Economic conditions; History; Labor Unions; Politics and government; Social conditions; Working class

Michel Chartrand : les dires d'un homme de parole - Foisy, Fernand (PCL/Petite collection Lanctôt, 2012)
"Michel Chartrand/Les dires d'un homme de parole" est composé d'extraits de discours et d'entrevues qui s'échelonnent sur près de trente ans de vie syndicale active. Ces textes, ces réflexions, ces discours témoignent d'une même volonté, parfois provocatrice, de dénoncer la bêtise et l'injustice où qu'elles soient. Michel Chartrand est un des plus anciens leaders syndicaux du Québec. Depuis qu'il milite en faveur des plus démunis de la société, les gouvernements se sont succédé, les uns ont été remplacés par d'autres, parfois plus progressistes, et ses propos demeurent toujours d'actualité. Ce qu'il dénonçait durant les années soixante l'appauvrissement des classes populaires, le gaspillage et la dilapidation honteuse de nos richesses, l'insécurité des travailleurs, le manque de prévoyance des grands patrons d'industrie doit toujours l'être aujourd'hui. Et ce qu'il pronait hier la justice sociale, la solidarité entre les humains, la liberté d'expression fait encore partie des grandes priorités de l'heure. --Résumé de l'éditeur
Keywords: Biographies; Chartrand, Michel, 1916- Citations; Chartrand, Michel, 1916- Entretiens; Chartrand, Michel, 1916- Pensée politique et sociale; Dirigeants syndicaux Québec (Province) Biographies; Labor leaders; Labor leaders Québec (Province) Biography; Québec; Syndicalism; Syndicalism Québec (Province); Syndicalisme Québec (Province)

May Day: A Graphic History of Protest - Folvik, Robin; Graphic History Collective (Group) (Between the Lines, 2012)
[This booklet] traces the development of International Workers’ Day, May 1st, against the ever-changing economic and political backdrop in Canada. Recognizing the importance of work and the historical struggles of workers to improve their lives, with a particular focus on the struggles of May 1st, the comic includes the reader as part of this history, and the story concludes that “We are all part of this historical struggle; it’s our history and our future." --Publisher's description

Le péril rouge: la première guerre canadienne contre le terrorisme, 1918-1919 - Francis, Daniel (Collection Mémoire des Amériques, 2012)
À la fin de la Première Guerre mondiale, le Canada menace de basculer dans une révolution sociale. Rassemblements et mobilisations des milieux ouvriers se succèdent durant l’hiver 1918-1919 et culminent avec la grève générale de Winnipeg en mai-juin 1919. Le mouvement est finalement écrasé par l’armée sur l’ordre de Robert Borden, premier ministre de l’époque. Cette suite d’événements, qui correspond dans les faits à un conflit de travail généralisé, est immédiatement associée par les autorités à la menace d’une révolution bolchevique. Le gouvernement et les médias lancent une grande campagne de diabolisation à l’endroit des chefs syndicaux et autres leaders politiques. Le but, bien évidemment, est d’user de la peur que suscitent partout les rouges pour étouffer le conflit social, et d’obtenir le soutien de l’opinion publique pour l’éradication de toute activité politique jugée radicale. Fondé sur des documents officiels et des témoignages de première main, cet ouvrage raconte un épisode méconnu mais déterminant de l’histoire canadienne. La campagne contre « le péril rouge » a joué un rôle fondamental dans la répression des conflits de travail de l’entre-deux-guerres. Depuis, la même recette a été utilisée pour les mêmes raisons. En outre, les parallèles avec la guerre actuelle contre le terrorisme se font sans effort. Aujourd’hui comme hier, les libertés d’expression et de contestation de l’ordre établi sont contraintes au nom d’une sécurité nationale aux frontières desquelles semblent s’arrêter les droits civils. --Résumé de l'éditeur
Keywords: Anticommunisme; Grève générale, Winnipeg, Man., 1919; Histoire; Influence

Constitutional Labour Rights in Canada: Farm Workers and the Fraser Case - Fudge, Judy; Tucker, Eric; Faraday, Fay (Irwin Law, 2012)
On 29 April 2011, the Supreme Court of Canada released its much-anticipated decision in Attorney General of Ontario v Fraser, which dealt with the scope of constitutional protection of collective bargaining. The case involved a constitutional challenge to an Ontario statute on the grounds that it violated agricultural workers’ freedom of association and right to equality by excluding them from the statutory protection that is available to virtually all other private sector workers and by failing to provide them with alternative legislative support for meaningful and effective collective bargaining rights. Although the Court upheld the constitutionality of the legislation by an eight to one majority, it provided four different, and incommensurable, sets of reasons. For the union that instigated the litigation, Fraser is a defeat. For the labour movement and their advocates, Fraser is ambiguous. What is clear, however, is that the Supreme Court of Canada was badly divided over the scope of protection that freedom of association provides to the right to bargain collectively. This collection of original essays untangles the two stories that are intertwined in the Fraser decision—the story of the farm workers and their union’s attempt to obtain rights at work available to other working people in Ontario, and the tale of judicial discord over the meaning of freedom of association in the context of work. The contributors include trade unionists, lawyers, and academics (several of whom were involved in Fraser as witnesses, parties, lawyers, and interveners). The collection provides the social context out of which the decision emerged, including a photo essay on migrant workers, while at the same time illuminating Fraser’s broader jurisprudential and institutional implications. --Publisher's description
Keywords: Agricultural laborers; Canada. Arbeitsrecht. Verfassungsrecht; Canada. Collective bargaining; Canada. Employee rights; Canada. Freedom of association; Canada. Liberté d'association; Canada. Migrant agricultural laborers; Canada. Négociations collectives; Canada. Personnel; Canada. Travailleurs agricoles; Canada. Travailleurs agricoles migrants; Droit; Droits; Law and legislation; Legal status, laws, etc.

Negotiating Risk, Seeking Security, Eroding Solidarity: Life and Work on the Border - Gibbs, Holly; Yates, Charlotte A. B. (Charlotte Alyce Bronwen); Leach, Belinda (Fernwood Publishing, 2012)
Through a series of interviews with workers in the automotive parts industry, Negotiating Risk argues that the restructuring of labour markets and welfare states, paired with firm-level work and management reorganization, has exposed working-class families to greater levels of job risk and insecurity. Focusing on workers in Canada and Mexico and using a gender and race analysis, this book paints a bleak portrait of the lives of working people, where workers and their families continually renegotiate the effects of neo-liberal economic and social change. These changes see individuals working harder, longer and travelling further from home to keep their jobs, while straining familial and community relations and eroding the basis for worker solidarity and collective action. --Publisher's description. Contents: Negotiating risk, seeking security, eroding solidarity -- Labour markets, the state and work through the lens of the automotive parts industry -- Communities and their labour markets -- Experiencing risk and seeking security -- Gendered practices of coping with risk and insecurity -- Sustaining livelihoods through mobility -- Whither solidarity?
Keywords: Canada. Automobile supplies industry; Canada. Automobiles; Canada. Labor market; Canada. Labor mobility; Canada. Working class families; Labor market; Mexico. Automobile supplies industry; Mexico. Labor mobility; Mexico. Working class families; Mexique. Automobiles

Breccia: Haiku and Related Forms - Golas, Irene; Fay, Ignatius (Irene Golas, Ignatius Fay, Lulu.com, 2012)
We chose Breccia as our title to reflect the nature of the [poetry] collection and our geographical location in Sudbury, Ontario. ...One section of this book, "Sudbury Breccia," grew out of a few poems about that northern mining town. We were attracted to the idea of examining life in such a town from World War II into the new millennium as seen through the eyes of a haiku poet. The diverse cultural mix of the miners themselves further enhances the breccia theme. The earliest miners were, primarily, a mélange of European immigrants who relocated to find a better life. This potpourri was enriched by large numbers of immigrants and displaced persons fleeing a war-ravaged Europe. The result was a northern Ontario mining culture with a distinctly varied foundation. --From authors' introduction. Six haiku by Ignatius Fay: headlamps off / inky black and the sounds / of shifting rock -- dad's St. Christopher / black with sweat / and mine dust -- two p.m. / the school shudders / with the mine's daily blast -- moving day / his father's job lost / to a Scooptram -- retired from mining / the school janitor's limp / worse in autumn -- played-out mine site - / the green of young thistles / in rust-stained soil. Tanka by Ignatius Fay: Levack North Mine / sixteen-hundred-foot level / the weight / of three billion years / over my head.

The Canadian Labour Movement: A Short History - Heron, Craig (Lorimer, 2012)
[H]istorian Craig Heron tells the story of Canada's workers from the mid-nineteenth century through to today, painting a vivid picture of key developments such as the birth of craft unionism, the breakthroughs of the fifties and sixties, and the setbacks of the early twenty-first century. This new edition has been completely updated, including a substantial new chapter that covers the period from 1995 to 2011. In this chapter, Heron describes the rise of globalization and the restructuring of the private sector that began in the nineties and continues today. The results have been catastrophic for Canadian working people as plants closed and union activities were curtailed. As the political right succeeded in dominating public debate during this period, workers suffered ever greater losses: fewer and more precarious jobs, rising unemployment, stagnating wages, and increases in poverty. Only with the crash of 2008 and the Occupy Wall Street movement has space for the political left and labour begun to open up once again. [This] is the definitive book for anyone who is interested in understanding the origins, achievements, and challenges of labour and social justice movements in Canada.--Publisher's description
Keywords: Histoire; History; Labor Unions; Syndicats

Legislated Inequality: Temporary Labour Migration in Canada - Lenard, Patti Tamara; Straehle, Christine (McGill-Queen's University Press, 2012)
Historically, Canada has adopted immigration policies focused on admitting migrants who were expected to become citizens. A dramatic shift has occurred in recent years as the number of temporary labourers admitted to Canada has increased substantially. Legislated Inequality critically evaluates this radical development in Canadian immigration, arguing that it threatens to undermine Canada's success as an immigrant nation. Assessing each of the four major temporary labour migration programs in Canada, contributors from a range of disciplines - including comparative political science, philosophy, and sociology - show how temporary migrants are posed to occupy a permanent yet marginal status in society and argue that Canada's temporary labour policy must undergo fundamental changes in order to support Canada's long held immigration goals. The difficult working conditions faced by migrant workers, as well as the economic and social dangers of relying on temporary migration to relieve labour shortages, are described in detail. Legislated Inequality provides an essential critical analysis of the failings of temporary labour migration programs in Canada and proposes tangible ways to improve the lives of labourers. --Publisher's description

The Punjabis in British Columbia: Location, Labour, First Nations, and Multiculturalism - Nayar, Kamala E. (Kamala Elizabeth) (McGill-Queen's studies in ethnic history, 2012)
In this richly detailed study, Kamala Nayar documents the social and cultural transformation of the Punjabi community in British Columbia. From their initial settlement in the rural Skeena region to the communities that later developed in larger urban centres, The Punjabis in British Columbia illustrates the complex and diverse experiences of an immigrant community that merits greater attention. Exploring themes of gender, employment, rural and urban migrant life, and the relationships between the Punjabis and surrounding First Nations and other immigrant groups, Nayar creates a portrait of a community in transition. Shedding light on the ways in which economic circumstances affect immigrant communities, Nayar presents findings from interviews conducted with over one hundred participants. She details the relocation of Punjabi populations from the Skeena region to British Columbia's lower mainland during the decline of the forestry and fishery industries, how their second migration changed their professional and personal lives, and how their history continues to shape the identities and experiences of Punjabis in Canada today. A nuanced look at the complexities of social and cultural adaptation, The Punjabis in British Columbia adds an essential perspective to what it means to be Canadian. --Publisher's description
Keywords: Panjabis (South Asian people) -- British Columbia -- Skeena River Region -- Economic conditions -- 20th century -- Case studies

Jobs and Justice: Fighting Discrimination in Wartime Canada, 1939-1945 - Patrias, Carmela (University of Toronto, 2012)
Despite acute labour shortages during the Second World War, Canadian employers—with the complicity of state officials—discriminated against workers of African, Asian, and Eastern and Southern European origin, excluding them from both white collar and skilled jobs. Jobs and Justice argues that, while the war intensified hostility and suspicion toward minority workers, the urgent need for their contributions and the egalitarian rhetoric used to mobilize the war effort also created an opportunity for minority activists and their English Canadian allies to challenge discrimination. Juxtaposing a discussion of state policy with ideas of race and citizenship in Canadian civil society, Carmela K. Patrias shows how minority activists were able to bring national attention to racist employment discrimination and obtain official condemnation of such discrimination. Extensively researched and engagingly written, Jobs and Justice offers a new perspective on the Second World War, the racist dimensions of state policy, and the origins of human rights campaigns in Canada. --Publisher's description
Keywords: Civil rights; Discrimination in employment; Employment; Government policy; History; Minorities; Race relations; Racism

Union Power: Solidarity and Struggle in Niagara - Patrias, Carmela; Savage, Larry (Working Canadians: Books from the CCLH, 2012)
From factory workers in Welland to retail workers in St. Catharines, from hospitality workers in Niagara Falls to migrant farm workers in Niagara-On-The-Lake, Union Power showcases the role of working people in the Niagara region. Charting the development of the region's labour movement from the early nineteenth century to the present, Patrias and Savage illustrate how workers from this highly diversified economy struggled to improve their lives both inside and outside the workplace. Including extensive quotations from interviews, archival sources, and local newspapers, the story unfolds, in part, through the voices of the people themselves: the workers who fought for unions, the community members who supported them, and the employers who opposed them. Early industrial development and the appalling working conditions of the often vulnerable common labourer prompted a movement toward worker protection. Patrias and Savage argue that union power – power not built on profit, status, or prestige – relies on the twin concepts of struggle and solidarity: the solidarity of the shared interests of the working class and the struggle to achieve common goals. Union Power traces the evidence of these twin concepts through the history of the Niagara region's labour movement. --Publisher's description
Keywords: History; Labor Unions; Labor movement; Nigara Peninsula

Boom, Bust and Crisis: Labour, Corporate Power and Politics in Canada - Peters, John (Labour in Canada (Halifax, N.S.), 2012)
Boom, Bust, and Crisis addresses...how work has changed across Canada, from the auto and steel industries of Ontario, to the tar sands of Northern Alberta and First Nations casinos in Saskatchewan. This edited collection explains the massive lay-offs in unionized manufacturing industries, the expansion of low-wage work and the rise of increasingly aggressive employers by critically examining Canada’s political economy and assessing the impact of government policy and labour market deregulation on Canada’s workers. The book also explores the recent policy changes to employment standards and health and safety protection in the context of neoliberal globalization. Written by leading political scientists, sociologists and journalists in concise, accessible language, this volume provides a rich and vibrant assessment of why some businesses have boomed while others have failed and why, through it all, Canadian workers have paid the price. --Publisher's description. Contents: Pt.1. The shifting political landscape. Free markets and the decline of unions and good jobs / John Peters -- The spoils of the Tar Sands: profits, work and labour in Alberta / Diana Gibson and Regan Boychuk -- Boom, bust, and bluster: Newfoundland and Labrador's "oil boom" and its impacts on labour / Sean T. Cadigan -- Steel City meltdown: Hamilton and the changing Canadian steel industry / Stephen R. Arnold -- Pt.2. Deregulation and changes in provincial labour market policy, politics and institutions. The biggest roll-back of worker rights in Canadian history: the Campbell government and labour market deregulation in British Columbia / David Fairey, Tom Sandhorn and John Peters -- Whither the Quebec model? Boom, bust and Quebec labour / Peter Graefe. Pt.3. New challenges facing labour organizing, health and safety. Indigenous workers, casino development and union organizing / Yale D. Belanger -- Precarious employment and occupational health and safety in Ontario / Wayne Lewchuk, Marlea Clarke and Alice de Wolff.
Keywords: Business and politics; Economic conditions; Employee rights; Industrial relations; Labor policy

Dynamic Negotiations: Teacher Labour Relations in Canadian Elementary and Secondary Education - Queen's University (Kingston, Ont.). School of Policy Studies (Queen's Policy Studies Series, 2012)
Taking an inter-provincial comparative approach, Dynamic Negotiations identifies potential avenues of reform. Academic and legal experts describe and analyse the history, current structure, and functioning of bargaining in public elementary and secondary schools in six key jurisdictions - Alberta, British Columbia, Manitoba, Ontario, Quebec, and Newfoundland - representing a spectrum of approaches. This is a vital area of public policy that is much discussed but not well enough understood. The volume is a valuable resource for policy-makers, academics, and practitioners in education and labour relations. --Publisher's description. Contents: Introduction: Labour Relations in Primary and Secondary Canadian Education / Sara Slinn and Arthur Sweetman -- Crosscurrents: Comparative Review of Elementary and Secondary Teacher Collective Bargaining Structures in Canada / Karen Schucher and Sara Slinn -- The Great Divide: School Politics and Labour Relations in British Columbia before and after 1972 / Thomas Fleming -- Conflict without Compromise: The Case of Public Sector Teacher Bargaining in British Columbia / Sara Slinn -- Oil and Ideology: The Transformation of K-12 Bargaining in Alberta / Kelly Williams-Whitt -- Teacher Collective Bargaining in Manitoba / Valerie J. Matthews Lemieux -- The Evolution of Teacher Bargaining in Ontario / Joseph B. Rose -- Collective Bargaining for Teachers in Ontario: Central Power, Local Responsibility / Elizabeth Shilton -- The Centralization of Collective Bargaining in Ontario's Public Education Sector and the Need to Balance Stakeholder Interests / Brendan Sweeney, Susan McWilliams, and Robert Hickey -- Labour Relations in the Quebec K-11 Education Sector: Labour Regulation under Centralization / Jean-Noël Grenier and Mustapha Bettache -- K-12 Teacher Collective Bargaining in Newfoundland and Labrador / Travor C. Brown.
Keywords: Collective bargaining; Public schools; Teachers; Teachers' unions

Rethinking the Politics of Labour in Canada - Ross, Stephanie; Savage, Larry (Labour in Canada (Halifax, N.S.), 2012)
Though the Canadian labour movement’s postwar political, economic and social achievements may have seemed like irrevocable contributions to human progress, they have proven to be anything but. Since the mid-1970s, labour’s political influence and capacity to defend, let alone extend, these gains has been seriously undermined by the strategies of both capitalist interests and the neoliberal state. Electoral de-alignment and the decline of class-based voting, bursts of unsustained extra-parliamentary militancy and a general lack of influence on state actors and policy outcomes all signal that the labour movement is in crisis. Despite much experimentation in an attempt to regain political clout, labour continues to experience deep frustration and stagnation. As such, the labour movement’s future political capacities are in question, and the need for critical appraisal is urgent. Understanding how and why workers were able to exert collective power in the postwar era, how they lost it and how they might re-establish it is the central concern of Rethinking the Politics of Labour in Canada. With essays from established and emerging scholars from a wide range of disciplines, this collection assesses the past, present and uncertain future of labour politics in Canada. Bringing together the traditional electoral-based aspects of labour politics with analyses of the newer and rediscovered forms of working-class organization and social movement-influenced strategies, which have become increasingly important in the Canadian labour movement, this book seeks to take stock of these new forms of labour politics, understand their emergence and assess their impact on the future of labour in Canada. --Publisher's description
Keywords: History; Labor Unions; Labor movement; Political activity; Political aspects

This Great National Object: Building the Nineteenth-Century Welland Canals - Styran, Roberta M. (Roberta McAfee); Taylor, Robert R. (McGill-Queen's University Press, 2012)
[The authors] recount the story of the canals, with particular emphasis on the experiences of the engineers, contractors, and labourers who built the inland waterways between 1824 and 1889. Making extensive use of the National Archives and the Archives of Ontario, Styran and Taylor unveil previously unpublished information about the construction of the canals, including technical plans and drawings from a wide variety of sources. They illustrate the technical and management intricacies of building a navigational trade and commerce lifeline while also revealing the vivid characters - from businessman William Hamilton Merritt to engineer John Page - who inspired the project and drove it to completion. The history of the Welland Canals is a gripping tale of epic proportions. Given the ongoing importance of the Great Lakes in the North American economy, interest in the St. Lawrence Seaway - of which the Welland is "the Great Swivel Link" - and the relevance of labour history, This Great National Object will be of interest to enthusiasts and historians alike. --Publisher's description
Keywords: Histoire; History

Company Towns: Corporate Order and Community - White, Neil (University of Toronto Press, 2012)
Company towns are often portrayed as powerless communities, fundamentally dependent on the outside influence of global capital. Neil White challenges this interpretation by exploring how these communities were altered at the local level through human agency, missteps, and chance. Far from being homogeneous, these company towns are shown to be unique communities with equally unique histories. Company Towns provides a multi-layered, international comparison between the development of two settlements—the mining community of Mount Isa, Queensland, Australia, and the mill town of Corner Brook, Newfoundland, Canada. White pinpoints crucial differences between the towns' experiences by contrasting each region's histories from various perspectives—business, urban, labour, civic, and socio-cultural. Company Towns also makes use of a sizable collection of previously neglected oral history sources and town records, providing an illuminating portrait of divergence that defies efforts to impose structure on the company town phenomenon. --Publisher's description
Keywords: Community life; Company towns; Corporations; Economic conditions; History; Social aspects; Social conditions

The Colonization of Mi'kmaw Memory and History, 1794-1928: The King V. Gabriel Sylliboy - Wicken, William Craig (University of Toronto Press, 2012)
In 1927, Gabriel Sylliboy, the Grand Chief of the Mi'kmaw of Atlantic Canada, was charged with trapping muskrats out of season. At appeal in July 1928, Sylliboy and five other men recalled conversations with parents, grandparents, and community members to explain how they understood a treaty their people had signed with the British in 1752. Using this testimony as a starting point, William Wicken traces Mi'kmaw memories of the treaty, arguing that as colonization altered Mi'kmaw society, community interpretations of the treaty changed as well. The Sylliboy case was part of a broader debate within Canada about Aboriginal peoples' legal status within Confederation. In using the 1752 treaty to try and establish a legal identity separate from that of other Nova Scotians, Mi'kmaw leaders contested federal and provincial attempts to force their assimilation into Anglo-Canadian society. Integrating matters of governance and legality with an exploration of historical memory, The Colonization of Mi'kmaw Memory and History offers a nuanced understanding of how and why individuals and communities recall the past."--Publisher's description. Contents: Part 1: Why the Men Testified. 1. Accounting for Alex Gillis's actions: the Mi'kmaq in rural society -- 2. Why Nova Scotia prosecuted Gabriel Sylliboy -- 3. Moving to appeal: Mi'kmaw and government motivations. Part 2: How the Men Remembered. 4. Parents, grandparents, and great grandparents, 1794-1853. 5. Reserve life, 1850-1881: remembering the treaty. Part 3: Why the Men Remembered. 6. The demography of Mi'kmaw communities, 1871-1911 -- 7. Moving into the city: the King's Road Reserve and the politics of relocation. Appendix: The Federal and DIA censuses, 1871-1911.
Keywords: Aspect social; Colonisation; Colonization; Government policy; Histoire. Collective memory. Memory; Histoire. Micmac (Indiens); History. Micmac (Indiens); History. Micmac Indians; Micmac Indians; Nouvelle-cosse; Nouvelle-cosse. Micmac (Indiens); Nouvelle-cosse. Mmoire; Nouvelle-cosse. Mmoire collective; Nova Scotia; Nova Scotia. Collective memory; Nova Scotia. Memory; Nova Scotia. Micmac Indians; Politique gouvernementale; Social aspects; Social aspects. Micmac Indians. Micmac Erinnerung

Indigenous Women and Work: From Labor to Activism - Williams, Carol (University of Illinois Press, 2012)
The essays in [this book] create a transnational and comparative dialogue on the history of the productive and reproductive lives and circumstances of Indigenous women from the late nineteenth century to the present in the United States, Australia, New Zealand/Aotearoa, and Canada. Surveying the spectrum of Indigenous women's lives and circumstances as workers, both waged and unwaged, the contributors offer varied perspectives on the ways women's work has contributed to the survival of communities in the face of ongoing tensions between assimilation and colonization. They also interpret how individual nations have conceived of Indigenous women as workers and, in turn, convert these assumptions and definitions into policy and practice. The essays address the intersection of Indigenous, women's, and labor history, but will also be useful to contemporary policy makers, tribal activists, and Native American women's advocacy associations. --Publisher's description
Keywords: Employment; Employment. Native women; Indigenous women